Analisis Perilaku Konsumtif Mahasiswa pada Penggunaan E-commerce dalam Perspektif Maqashid al-Syariah - Fadhilah, Nurul; Nurmala, Mia (Universitas Islam Lamongan, 2024)
This research is based on many of university students who use e-commerce. The purpose of this study is to find out students' behavior in buying goods in e-commerce and whether they use the principles of maqashid al-sharia or not. The principles of maqashid al-sharia used are the maintenance of religion (hifz al-din), the maintenance of the soul (hifz al-nafs), the maintenance of reason (hifz al-‘aql), the maintenance of offspring (hifz al-nasl), the maintenance of assets (hifz al-mal), and the maintenance of the environment (hifz al-biah). This research is qualitative research with a phenomenological abbreviation. The sampling technique in this study is purposive sampling. This sample of research totaled 45 1st level students of Sultan Ageng Tirtayasa University. The results of the study show that students have not fully used the principles of maqashid sharia in the use of e-commerce, so students behave consumptuantly. In the principle of religious protection, it is known that not all students buy goods with the intention of worship, in the principle of preserving reason, students cannot decide properly the priority of the goods to be purchased, on the principle of spiritual care, students cannot resist the lust to buy goods that are by the usefulness, on the principle that the descendants of students have not been able to save money for the future, In the principle of assets, students were found to use the pay later feature. And on the principle of protecting the environment, students still need education in the recycling system of goods that have been purchased.